Nilai-Nilai Fundamental dan Pengaruhnya terhadap Beta Saham pada Perusahaan yang Listed di Bursa Efek Indonesia dalam Kategori LQ45 Periode 2012-2014 - Khobibah, Inti; Handayani, Dwi; Wibisono, Haris (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
This study aims to demonstrate empirically the effect of leverage, earning variability, accounting beta, earning per share, price earning ratio, price book value, dividend yield and trading volume of the stock beta in companies listed on the Indonesia Stock Exchange in category LQ45 period 2012- 2014. The sample used in this study is the companies included in the index LQ45 over the years 2012 to 2014 on the Indonesian Stock Exchange. Total sample of 60 companies that are determined by purposive sampling method. This study uses multiple regression method with SPSS version 17 to examine the effect of leverage, earnings variability, beta accounting, earnings per share, the price earnings ratio, price-book value, dividend yield and trading volume of the stock beta. The results of this study indicate that the variable leverage, earning variability, accounting beta, earning per share, the price earning ratio, price book value and dividend yield no effect on beta stocks. While the trading volume variable positive effect on beta stocks.